Informe sobre los Artículos de acuerdo a las Prioridades de la U.N.A.H. - La Editora, (La Revista de Derecho, 2015)
DOI: http://dx.doi.org/10.5377/lrd.v35i0.1788 Revista de Derecho, Vol. 34, Nº 1, Año 2013: 162-163